2018
DOI: 10.1093/cid/ciy553
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and Cost-utility of the Adherence Improving Self-management Strategy in Human Immunodeficiency Virus Care: A Trial-based Economic Evaluation

Abstract: Base case analyses suggests that over a period of 15 months, AIMS may be costlier, but also more effective than TAU. All additional analyses suggest that AIMS is cheaper and more effective than TAU. This trial-based economic evaluation confirms and complements a model-based economic evaluation with a lifetime horizon showing that AIMS is cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, not all studies explicitly stated whether they applied a CEA or CUA approach. Only three out of the 29 studies explicitly reported to have undertaken a CUA [ 35 37 ] and one study was explicit about having conducted both a CEA and CUA [ 38 ]. Modelling was used in all but two studies, which were trial-based [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, not all studies explicitly stated whether they applied a CEA or CUA approach. Only three out of the 29 studies explicitly reported to have undertaken a CUA [ 35 37 ] and one study was explicit about having conducted both a CEA and CUA [ 38 ]. Modelling was used in all but two studies, which were trial-based [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vaccination and screening interventions dominated, and involved stand-alone vaccination [ 45 , 50 52 ], vaccination in addition to screening [ 40 , 53 56 ], vaccination of girls and boys [ 43 , 47 ], sex-neutral vaccination [ 49 ], screening (stand-alone) [ 41 , 57 59 ], screening in addition to testing [ 60 ] and screening after vaccination [ 61 ]. Other interventions involved test and treat interventions including PrEP (Pre-Exposure Prophylaxis) [ 42 , 62 ], testing and linkage to care [ 37 ] and opt-out testing strategy [ 46 ]; expedited partner treatment [ 46 ], population-level treatment expansion [ 44 ], (on-demand) PrEP [ 35 , 63 ], treatment adherence interventions [ 38 ], guided internet-based behaviour intervention [ 36 ] and financial incentives [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations